2007
DOI: 10.1002/art.23042
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kawasaki disease is associated with reverse regulation of soluble receptor for advance glycation end products and its proinflammatory ligand S100A12

Abstract: Objective. Receptor for advanced glycation end products (RAGE) serves as a pattern recognition receptor for several endogenous ligands that are potent inducers of inflammation. By activating endothelial cells and leukocytes, RAGE augments recruitment of leukocytes to sites of inflammation, which is a key process, especially in vasculitis. Soluble RAGE (sRAGE) acts as a naturally occurring inhibitor of RAGE by neutralizing proinflammatory ligands, e.g., S100A12. This neutrophil-derived protein has been reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
52
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 38 publications
10
52
0
1
Order By: Relevance
“…In keeping with previous reports, our study confirms the utility of S100A12 as a diagnostic biomarker for SJIA (3,26). Our data additionally show that S100A12 may have potential to distinguish KD from SJIA, although replication of this finding in a larger cohort is essential.…”
Section: Discussionsupporting
confidence: 92%
“…In keeping with previous reports, our study confirms the utility of S100A12 as a diagnostic biomarker for SJIA (3,26). Our data additionally show that S100A12 may have potential to distinguish KD from SJIA, although replication of this finding in a larger cohort is essential.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, patients with acute Kawasaki disease had very low sRAGE concentrations and a high ratio of the proinflammatory RAGE ligand S100A12 to sRAGE when compared with controls. After successful treatment with intravenous Ig, both of these markers returned close to normal (20). Similarly, our previous study showed that sRAGE concentrations tend to decline at seroconversion to autoantibody positivity both in an animal model of autoimmune diabetes and in a small group of prediabetic children (10).…”
supporting
confidence: 71%
“…A decline in circulating soluble RAGE has also been shown in children during active autoimmune disease, such as Kawasaki disease or systemic onset juvenile idiopathic arthritis [42]. Decreases in plasma soluble RAGE were also seen in samples from children who progressed to type 1 diabetes at seroconversion to autoantibodies, compared with samples obtained before seroconversion.…”
Section: Discussionmentioning
confidence: 86%